2017
DOI: 10.1590/1678-4499.2016391
|View full text |Cite
|
Sign up to set email alerts
|

Copper and zinc accumulation, fractionation and migration in vineyard soils from Santa Catarina State, Brazil

Abstract: ABSTRACT:The purpose of this study was to evaluate Cu and Zn migration and fractions in sandy soil of vineyards. In Urussanga (SC), Brazil, soil samples were collected from a 4-year-old and 15-yearold vineyard, and from a forested area. In the soils, the chemical characteristics of Cu and Zn were analyzed by the EDTA method, which determines the fraction available in soil; 3050B method of the USEPA for total concentrations, which represents the pseudo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
1
13
2
Order By: Relevance
“…Zinc was highly mobile in Vertisol-I, as it observed the highest MF 1.81% (Table 1) and the mobility factor of Zn follows the order of Vertisol>Inceptisol>Entisol>Alfisol. However, it has been reported that Zn is mostly associated with the low molecular weight organic acids and low adsorption capacity of Zn in sand particles increased its mobility (Brunetto et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc was highly mobile in Vertisol-I, as it observed the highest MF 1.81% (Table 1) and the mobility factor of Zn follows the order of Vertisol>Inceptisol>Entisol>Alfisol. However, it has been reported that Zn is mostly associated with the low molecular weight organic acids and low adsorption capacity of Zn in sand particles increased its mobility (Brunetto et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between it is r = 0.80 (p< 0.05), indicating probable origin from the same factors. Brunetto et al (2018) found that increases in Cu and Zn yields are normal in conventional vineyard areas, increasing with the time of use under this crop. The authors also highlight the presence of Cu in forms more available to plants, due to the greater affinity of Zn with more energetic connections with the mineral fraction of the soil.…”
Section: Graph 1: Average Soil Ph Values For Different Land Usesmentioning
confidence: 91%
“…In Tállya, the SOM content strongly influenced the EDTA extracted contents of Cu showing a positive correlation (Table 5). The quantity of PTEs extracted by EDTA can be highly dependent on mineral phases and their respective total contents (Couto et al 2014;Brunetto et al 2014Brunetto et al , 2018Duplay et al 2014;Fernández-Calviño et al 2012). Significant correlation between total Mn contents and PTEs (except for Cu) may indicate their association with the reactive surface sites of Mn oxides (Table 5).…”
Section: Total and Bioavailable Contents Of Ptes In The Vineyard Soilsmentioning
confidence: 99%